Phylogenetic and evolutionary aspects of Paracoccidioides brasiliensis reveal a long coexistence with animal hosts that explain several biological features of the pathogen - Bagagli, Eduardo; Bosco, Sandra M. G.; Theodoro, Raquel Cordeiro; Franco, Marcello (Elsevier B.V., 2006)
The habitat of the mycelial saprobic form of Paracoccidio ides brasiliensis, which produces the infectious propagula, has not been determined and has proven difficult for mycologists to describe. The fungus has been rarely isolated from the environment, the disease has a prolonged latency period and no outbreaks have been reported. These facts have precluded the adoption of preventive measures to avoid infection. The confirmation of natural infections in nine-banded armadillos (Dasypus novemcinctus) with P. brasiliensis, in high frequency and wide geographic distribution, has opened new avenues for the study and understanding of its ecology. Armadillos belong to the order Xenarthra, which has existed in South America ever since the Paleocene Era (65 million years ago), when the South American subcontinent was still a detached land, before the consolidation of what is now known as the American continent. on the other hand, strong molecular evidence suggests that P. brasiliensis and other dimorphic pathogenic fungi - such as Blastomyces dermatitidis, Coccidioides immitis and Histoplasma capsulatum - belong to the family Onygenaceae sensu Into (order Onygenales, Ascomycota), which appeared around 150 million years ago.P. brasiliensis ecology and relation to its human host are probably linked to the fungal evolutionary past, especially its long coexistence with and adaptation to animal hosts other than Homo sapiens, of earlier origin. Instead of being a blind alley, the meaning of parasitism for dimorphic pathogenic fungi should be considered as an open two-way avenue, in which the fungus may return to the environment, therefore contributing to preserve its teleomorphic (sexual) and anamorphic (asexual) forms in a defined and protected natural habitat. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Paracoccidioides brasiliensis; dimorphic pathogenic fungi; infection; systemic mycoses; evolution; ecology